Cannabis on campus changing the dialogue in the wake of legalization - Beazley, Jonathan C.; Field, Stephanie Leigh (Routledge, 2018)
"Cannabis on Campus is a comprehensive resource on the implications of marijuana legalization for college campuses. It is essential reading for college administrators and other professionals responsible for overseeing drug policy and addressing marijuana use in higher education. The authors use their considerable experience in college alcohol and other drug (AOD) counseling to provide a sweeping look at the cannabis culture found in our universities. Chapters alternate between historical context, research and analysis, and student interviews, providing an evidence-based, nuanced understanding of the role of marijuana use in today's college campuses, as well as insights and recommendations for a post-legalization future."--Provided by publisher